DETERMINAN KEPATUHAN WAJIB PAJAK DALAM MEMBAYAR PAJAK BUMI DAN BANGUNAN PERDESAAN DAN PERKOTAAN (PBB-P2) DI KECAMATAN SELONG - Sofia Marwati; Elin Erlina Sasanti; Nurabiah Nurabiah (Universitas Dharmawangsa, 2023)
This study aims to examine the effect of tax knowledge, taxpayer awareness, andÂ fiscus service quality on taxpayer compliance in paying rural and urban land and building taxes in Selong District. This type of research is associative research uses primary data obtained through the distribution of questionnaires to 395 respondents who are taxpayers in Selong District. The data analysis technique in this study was carried out using the Partial Least Square (PLS) method using SmartPLS 3.0 software. The results of this study indicate that tax knowledge, taxpayer awareness, and fiscus service quality have a positive and significant effect on taxpayer compliance in paying rural and urban land and building taxes in Selong District. This research supports attribution theory ini explaining the factors that influence taxpayer compliance behavior. It is hoped that the results of this research can be input for local governments in increasing taxpayer compliance by providing regular and periodic tax outreach so that taxpayer knowledge and taxpayer awareness increases and always provides good sevice to taxpayers.Keywords: Tax Knowledge, Taxpayer Awareness, Fiscus Service Quality, Taxpayer Compliance